2022
DOI: 10.1186/s12894-022-01146-w
|View full text |Cite
|
Sign up to set email alerts
|

Extraosseous Ewing's sarcoma/peripheral primitive neuroectodermal tumour of the kidney: a case report and literature review

Abstract: Background Extraosseous Ewing's sarcoma/peripheral primitive neuroectodermal tumours(EWS/pPNETs) of the kidney are rare. Signs and symptoms are atypical in EWS patients. Presenting symptoms include haematuria, abdominal pain, or a palpable mass. A comprehensive review of the literature shows that it is difficult to make an accurate diagnosis based on physical examination alone. The imaging findings of EWS/pPNETs are nonspecific. We used contrast-enhanced ultrasound (CEUS) to diagnose an EWS/pPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…ESK frequently spreads to various locations in approximately 65% of patients, with the lungs, liver, and regional lymph nodes being the most commonly affected sites [ 4 ]. Our patient had metastases to the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ESK frequently spreads to various locations in approximately 65% of patients, with the lungs, liver, and regional lymph nodes being the most commonly affected sites [ 4 ]. Our patient had metastases to the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…ESK is an exceedingly rare and highly malignant entity, first reported by Seemayer et al in 1975 and approximately comprising less than 200 cases in the literature [12][13][14]. These tumors, which make up <1% of all renal tumors, have a much higher prevalence in males than females [4]. A meta-analysis done by Risi et al of 116 cases of ESK found that the median age was 28 years old and the most common presenting clinical symptoms included pain (54%), hematuria (29%), and renal mass (28%) [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations